2018
DOI: 10.1007/s10792-018-0969-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of four local anesthetics (tetracaine, proparacaine, lidocaine, and bupivacaine) on intraocular pressure in dogs

Abstract: We recommend using drugs that combine inducing longer anesthesia with producing the smallest change in IOP, such as bupivacaine and, subsequently, lidocaine. Tetracaine and proparacaine have a significant effect on IOP, and if these drugs are used, this effect should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…One recent study showed that tropicamide increased IOP in dogs by 8.8 ± 4.0 mmHg by 35 minutes post‐treatment compared to pre‐treatment, 31 while another study showed that the majority (60%) of dogs displayed 5 mmHg or less in IOP change post‐mydriasis 32 . Topical anesthetics, on the other hand, tend to reduce IOP readings 27,33,34 . However, attempts were made to reduce the overall effect of these medications on individual tonometer readings by randomization of the order with which each tonometer was used, and all readings were obtained within 10 minutes from the time of topical anesthetic and mydriatic application.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study showed that tropicamide increased IOP in dogs by 8.8 ± 4.0 mmHg by 35 minutes post‐treatment compared to pre‐treatment, 31 while another study showed that the majority (60%) of dogs displayed 5 mmHg or less in IOP change post‐mydriasis 32 . Topical anesthetics, on the other hand, tend to reduce IOP readings 27,33,34 . However, attempts were made to reduce the overall effect of these medications on individual tonometer readings by randomization of the order with which each tonometer was used, and all readings were obtained within 10 minutes from the time of topical anesthetic and mydriatic application.…”
Section: Discussionmentioning
confidence: 99%
“…Factors which could possibly cause discrepancies between the studies may include population differences in corneal thickness and curvature, 20 21 instrument technique and calibration, undetected pathology, stress, different pressure on vasculature in the neck, and choice of topical local anaesthetics 22 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies concerning the practice of topical nasal anesthesia before transnasal fiber‐optic laryngoscopy (TFL) have concluded that its use does not improve patient comfort during the examination . The most effective drug is tetracaine, which is an ester group and is hydrolyzed in the plasma …”
Section: Discussionmentioning
confidence: 99%